Imaging phenotypes of chronic obstructive pulmonary disease - Ley-Zaporozhan, Julia; Beek, Edwin J.R. van (Journal of magnetic resonance imaging, 2010)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of morbidity and mortality worldwide. COPD is defined by irreversible airflow obstruction. It is a heterogeneous disease affecting the airways and/or the parenchyma with different severity during the course of the disease. These different aspects of COPD can be addressed by imaging using a combination of morphological and functional techniques. Computed tomography (CT) is the technique of choice for morphological imaging of the lung parenchyma and airways. This morphological information is to be accomplished by functional information about ventilation and perfusion, mainly provided by magnetic resonance imaging (MRI). The comprehensive diagnostic possibilities of CT complemented by MRI will allow for a more sensitive detection, phenotype-driven characterization, and dedicated therapy monitoring of the disease. J. Magn. Reson. Imaging 2010;32:1340-1352. © 2010 Wiley-Liss, Inc.
Gesehen am 14.03.2023